Study on the Era of Visual Communication Art Design - Zang, Suran; Xu, Lianjiang; Sun, Haiyan (Journal of physics. Conference series, 2021)
With the continuous popularization and innovation of network technology, China and the world have gradually entered the era of all-media, and the influence of visual communication art on industrial design in the era of new media has gradually increased. This paper analyzes the contemporary characteristics of modern visual communication art design from several aspects, such as design characteristics, expression and communication, and proposes that in the new era of art design creation, technology and art should complement each other, realize multi-dimensional interaction with visual information as the boundary, and realize the concept of innovation based on the pursuit of life substance, which provides a more a wide range of ideas.